The credibility of NATO security guarantees from the Polish perspective (Economic and Political Thought, 2016)
The article distinguishes such risks for the credibility and effectivenessof NATO as a collective defence organisation in the short and medium termperspective, as tight defence budgets in key NATO countries, concentrationof a large part of the members of NATO on other risks than those associatedwith Art. 5, the reduction of US involvement in European security connectedwith permanently unequal distribution of costs in NATO and changes inpower in alliance countries that may undermine the transatlantic solidarityin the field of security. Referring to the theory of alliances and theories ofdeterrence the text argues that the credibility of alliance guarantee is alwayslimited and is subject to significant fluctuations over time.